Optimal design of passive energy dissipation systems based on Hx and H2 performances. - Yang, J.N (Earthquake engineering & structural dynamics.)
Passive energy dissipation devices (EDDs), such as viscous dampers, viscoelastic dampers, etc., have been used to effectively reduce the dynamic response of civil infrastructures, such as buildings and bridges, subject to earthquakes and strong winds. The design of these passive energy dissipation devices (EDDs) involves the determination of the optimal locations and the corresponding capacities. In this paper, we present two optimal design methodologies for passive EDDs based on active control theories, including Hx and H2 performances, respectively. The optimal design methodologies presented are capable of determining the optimal locations and the corresponding capacities of EDDs. Emphasis is placed on the application of linear matrix inequality (LMI) for the effective design of passive EDDs using the popular MATLAB toolboxes. One important advantage of the proposed approaches is that the computation of the structural response is not needed in the design process. The proposed optimal design methodologies have been applied to: (i) a 10 storey building and a 24 storey building both subject to earthquake excitations and (ii) a 76 storey wind excited benchmark building, to demonstrate the advantages of the proposed design methodologies over the conventional equal capacity design.